Beach sands deposite identification using very low frequency method in the Benteng Lubuk, Krueng Raya coastal area. Issue 1 (November 2021) - Jannah, M; Muhammad, M; Marwan; Jalil, Z
Abstract: The 2D subsurface identification work of iron sands in Benteng Lubuk, Krueng Raya was successfully studied using the very low frequency method based on resistivity mode (VLF-R). This study aims to identify iron sand deposits in coastal areas using electromagnetic inversion. The inversion process shows a conductivity zone of iron sand area, where the resistive layer is strongly covered by a conductive layer above it. High resistivity values were found at 80-100 m stations. This layer has a resistivity value between 20000 – 40000 m and the conductivity value tend to be low. It is estimated that at this point there will only be manifestations of iron sand or sea water intrusion, due to the location of the track close to the coastline.